PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS ANDROID UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR - Rizki Yan Saputra; Alexon (DIADIK, 2023)
This research is aimed to develop android-based interactive multimedia on Computer and Basic Network subject at TKJ major in Vocational high school grade X. The approach of this research is Research and Development (R&D) with 4-D (Four D)developmental model consisted of define, design, develop, disseminate. Research subject was teacher and students of Public Vocational High School Bengkulu. Data gathering technique used was consisted of expert assessment sheet, learning independence questionnaire, student’s test sheet and media is validated by media experts which then analyzed using Aiken’V formula. In order to conduct practicality test, media was analyzed using Kappa Moment. Then, T-test was used to analyze students’ learning independence and effectiveness of multimedia. Research remarks multimedia used is proper to use by students. Then, practicality test reveals that it is very practical. Multimedia used is effective which can be seen from students’ learning result. Thus, android-based interactive multimedia is proven to be able to improve students’ learning independence using adroid based interactive multimedia during learning process.